Bank business model as a supervisory perspective. Conditions and influences - Nosowski, Adam (Bankowy model biznesowy jako perspektywa nadzorcza – uwarunkowania i oddziaływania, 2017)
Analysing the banking business model as a supervisory perspective is a new way of monitoring the actions of supervised institutions, which significantly increases control. An additional analysis of banking business models can supply useful tools for understanding the nature of risks related to a given banking business model, and its influence on systemic risk. These tools are useful to market participants and regulation and supervisory institutions. The main goal of this article is an identification of contexts and conditions of the banking business model as a supervisory perspective. This approach allows to perceive its characteristics, aims, and methodology requirements. The supervisory perspective on business models was also compared to other practical and theoretical approaches, creating analytical context. An analysis of European guidelines for business models as a supplementary supervision practice, and their implementation in Poland was performed as well
Nauki o Finansach = Financial Sciences, 2017, Nr 2 (31), s. 66-78
Keywords: bank business model; business model analysis; supervisory review and evaluation process; model biznesowy banku; analiza modelu biznesowego; proces przeglądu i oceny nadzorczej